2009
DOI: 10.1080/09513590903015593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specific exercise training on bone mineral density in women with postmenopausal osteopenia or osteoporosis

Abstract: This protocol of weight training exercise did not significantly improve bone mineral density in postmenopausal women with osteopenia or osteoporosis, but in comparison to the control group, the results showed the importance of practising the specific exercise program for maintenance of bone health in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 18 publications
1
38
0
3
Order By: Relevance
“…Specifically, the most successful exercise programs to improve bone strength appear to be those that incorporate a diverse range of weight-bearing activities (e.g., skipping, dancing, jumping, and hopping) [3,4] ranging in magnitude from three to nine times body weight and which are performed three to five times per week, preferably on a daily basis, for 10-45 minutes per session [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the most successful exercise programs to improve bone strength appear to be those that incorporate a diverse range of weight-bearing activities (e.g., skipping, dancing, jumping, and hopping) [3,4] ranging in magnitude from three to nine times body weight and which are performed three to five times per week, preferably on a daily basis, for 10-45 minutes per session [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados difieren de otros estudios que han comunicado sobre el poco efecto de los programas de ejercicios sobre la masa ósea en mujeres pre y posmenopáusicas (12). No obstante, los hallazgos encontrados coinciden con los resultados de otros meta-análisis que confirman que el ejercicio físico tiene un efecto positivo en el incremento de la densidad mineral ósea (22).…”
Section: Discussionunclassified
“…A la luz de los resultados aquí encontrados, este tipo de ejercicio parece ser un factor importante para la prevención de la osteoporosis y la reducción del riesgo de fractura. Ya que además de mejorar la fuerza muscular, mejora el equilibrio y el ánimo en general (12).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…21,46 Previous studies have reported that RT is able to prevent bone demineralization in older women. 47,48 For instance, the study by de Matos, et al 48 reported that 12 weeks of weight training, among postmenopausal women with osteoporosis or osteopenia, did not significantly improve BMD (1.17%) at the lumbar spine in the exercise group (n=30). However, the control group (n=29) showed a significant loss in the spine BMD (2.26%).…”
Section: Effects Of Resistance Training On Bone Massmentioning
confidence: 99%